Adaptive control of mobile manipulators subject to external force and uncertainties. (9th July 2012) - Boukattaya, Mohamed; Damak, Tarak; Jallouli, Mohamed
This paper addresses the trajectory tracking control of a non-holonomic wheeled mobile manipulator subjected to uncertainties and external force. The proposed algorithm is robust adaptive control strategy where external force and uncertainties are compensated by adaptive update techniques. The proposed algorithm makes the robot follow simultaneously desired end-effector and platform trajectories in task space without violating the non-holonomic constraints. The system stability and the convergence of tracking errors are rigorously proved using a Lyapunov theory. Simulation results are given to illustrate the effectiveness of the proposed robust adaptive control law in comparison with a classical Computed Torque Controller (CTC).